Secrets of Quick Learning of a Foreign Language - Eshonkulova Madina Sanjar qizi (International Journal on Human-Computing Studies, 2022)
Life today cannot be imagined without foreign languages. As the process of globalization accelerates, learning a foreign language is becoming a modern requirement. Today, knowing English has become a simple requirement to be a good professional in any field. The question I asked myself while learning a foreign language was: "How can I learn a foreign language quickly? How can I speak a foreign language easily?" "Learning a language quickly, then speaking it quickly what's the secret 4 hours of language learning takes time to master the language perfectly? ”As a result of my many years of research, I have come to realize that the cause of the problem is the approach to language learning. I am learning a sixth language today because I understand a lot of mistakes and it seems easier to me than ever. I understand day by day that learning a foreign language is not as difficult as we imagined. The important thing for this is to be able to choose the best way to learn a foreign language. The Soviet methodology used in most of our educational institutions is outdated, and language learning today is more dependent on the learner than on the teacher.